The Evolution of Surgical Strategies for Pancreatic Neuroendocrine Tumors (Pan-NENs): Time-trend and Outcome Analysis From 587 Consecutive Resections at a High-volume Institution. Issue 4 (April 2019) - Landoni, Luca; Marchegiani, Giovanni; Pollini, Tommaso; Cingarlini, Sara; D'Onofrio, Mirko; Capelli, Paola; De Robertis, Riccardo; Davì, Maria V.; Amodio, Antonio; Impellizzeri, Harmony; Malpaga, Anna; Miotto, Marco; et al.
Abstract : Objective: The objective of the present analysis is 2-fold: first, to define the evolution of time trends on the surgical approach to pancreatic neuroendocrine neoplasms (Pan-NENs); second, to perform a complete analysis of the predictors of oncologic outcome. Background: Reflecting their rarity and heterogeneity, Pan-NENs represent a clinical dilemma. In particular, there is a scarcity of data regarding their long-term follow-up after surgical resection. Methods: From the Institutional Pan-NEN database, 587 resected cases from 1990 to 2015 were extracted. The time span was arbitrarily divided into 3 discrete clusters enabling a balanced comparison between patient groups. Analyses for predictors of recurrence and survival were performed, together with conditional survival analyses. Results: Among the 587 resected Pan-NENs, 75% were nonfunctioning tumors, and 5% were syndrome-associated tumors. The mean age was 54 years (±14 years), and 51% of the patients were female. The median tumor size was 20 mm (range 4 to 140), 62% were G1, 32% were G2, and 4% were G3 tumors. Time trends analysis revealed that the number of resected Pan-NENs constantly increased, while the size (from 25 to 20 mm) and G1 proportion (from 65% to 49%) decreased during the study period. After a mean follow-up of 75 months, recurrence analysis revealed that nonfunctioning tumors, tumor grade, N1 status, and vascular invasion were all independent predictors of recurrence. Regardless of size, G1 nonfunctioning tumors with no nodal involvement and vascular invasion had a negligible risk of recurrence at 5 years. Conclusions: Pan-NENs have been increasingly diagnosed and resected during the last 3 decades, revealing reliable predictors of outcome. Functioning and nodal status, tumor grade, and vascular invasion accurately predict survival and recurrence with resulting implications for patient follow-up. Abstract : Supplemental Digital Content is available in the text